2018
DOI: 10.22211/cejem/90801
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PolymerIc Binders on the RDX-based Explosive Response Character under Slow Cook-off Conditions

Abstract: Due to safety requirements, insensitive behaviour under slow thermal heating (cook-off) conditions is a desirable behaviour for today's munitions. In this paper a cook-off device is designed to test two groups of RDX-based PBX explosives. In the first group the binder type was varied and in the second group the binder content of the RDX-based explosive was changed. Eleven samples were examined in order to evaluate the influence of four different binders and seven different binder contents on the shell deformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…25–27 Recent experiments reported that the more gas generated by decomposition before thermal runaway, the greater the pre-damage caused and the lower the reaction intensity of slow cook-off. 28–31 Since the explosives rapidly combust and explode after entering from thermal decomposition to thermal runaway, the thermal pre-damage before this significantly influences the intensity of the reaction. Therefore, we used an adiabatic reaction calorimeter (ARC) to investigate the heat and gas release behaviour of HMX and PW/HMX between decomposition and thermal runaway.…”
Section: Resultsmentioning
confidence: 99%
“…25–27 Recent experiments reported that the more gas generated by decomposition before thermal runaway, the greater the pre-damage caused and the lower the reaction intensity of slow cook-off. 28–31 Since the explosives rapidly combust and explode after entering from thermal decomposition to thermal runaway, the thermal pre-damage before this significantly influences the intensity of the reaction. Therefore, we used an adiabatic reaction calorimeter (ARC) to investigate the heat and gas release behaviour of HMX and PW/HMX between decomposition and thermal runaway.…”
Section: Resultsmentioning
confidence: 99%
“…The cook-off resistant performance was tested with a smallscale cook-off test apparatus [18]. As shown in Figure 1, two CL-20/FOX-7 pellets(F16 3 32 mm) with 90 % theoretical maximum density were placed in small-scale cook-off bomb.…”
Section: Characterization and Testsmentioning
confidence: 99%
“…Amiya Kumar Nandi et al modified cyclotetramethylenetetranitramine with 1,3,5-Triamino-2,4,6-trinitrobenzene [ 23 ]. Xiang Yan et al designed a device to evaluate binder characteristics for high explosives [ 24 ]. Lu Zhang et al modified membranes with diisooctylsebacate as an excellent antibacterial agent [ 25 ].…”
Section: Introductionmentioning
confidence: 99%